2004
DOI: 10.1007/s00464-004-9090-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of skills in virtual laparoscopy and endoscopy

Abstract: Both simulators can distinguish between experienced and inexperienced subjects. Observed skills in simulated laparoscopy correlate with skills in simulated flexible endoscopy. This finding may have an impact on the design of training programs involving both procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Our study, like many others [1,6,7,12,14], has demonstrated that the endoscopic simulator can distin- guish between intermediately experienced and experienced endoscopists. Since well-designed prospective randomized studies have shown that simulators also improve the performance of residents in the operating room [10,16] as well as the endoscopy room [15], the question is not if but, rather, when simulators should be introduced into medical training.…”
Section: Discussionmentioning
confidence: 69%
“…Our study, like many others [1,6,7,12,14], has demonstrated that the endoscopic simulator can distin- guish between intermediately experienced and experienced endoscopists. Since well-designed prospective randomized studies have shown that simulators also improve the performance of residents in the operating room [10,16] as well as the endoscopy room [15], the question is not if but, rather, when simulators should be introduced into medical training.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, there is scant evidence to support the validity of GIMentor Colonoscopy (Table 4a) [28][29][30][31], with contrast validation shown for unspecified cases (end points: adverse events, insertion time, and identification of pathology). This situation is reversed for the gastroscopy simulations, with GIMentor having a level 2 recommendation for cases 1, 3, and 5 (end points: time, percentage of mucosa seen, and identification of pathology; Table 4b) [29][30][31][32][33][34]. The Accutouch Upper GI and ERCP simulations have very little published information available, with early face validation studies indicating poor validity for endoscopic appearance (Table 3b).…”
Section: Level Of Recommendation For Flexible Endoscopy Simulatorsmentioning
confidence: 87%
“…Several flexible endoscopy simulation models are available, each equipped with its own set of metrics. Many of them have been subjected to various validation processes, but there is a need to demonstrate transfer of simulator skills to the endoscopy suite [11,[17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%